Resíduo de pré-limpeza de soja como alimento volumoso na terminação de cordeiros em confinamento - Costa, Viviana Reboledo da (2020)
The objective of the experiment was to evaluate the performance, ingestive behavior, carcass characteristics and non-carcass components, as well as to perform an economical analysis of feedlot finished lambs with different levels of sorghum silage replacement by soybean pré cleaning waste as roughage in the diet of animals. Thirty-two male, non-castrated crossbred Texel x Ile de France lambs were weaned at 60 days of age. The animals were randomly distributed in a completely randomized experimental design with four treatments and eight replications. The treatments consisted of different levels of sorghum silage replacement by soybean pre-cleaning waste (% DM): 0%, 33.5%, 66.5%, or 100% substitution. The roughage: concentrate ratio was 45:55, based on dry matter. The animals were slaughtered as they reached a weight of 35 kg without fasting, which corresponds to 60% of their mothers' adult weight. The use of soybean pre-cleaning waste in substitution of sorghum silage as roughage in the diet of confined lambs does not alter the productive performance of the animals. In addition, feed costs decrease linearly as the level of sorghum silage substitution by this residue increases, which provides increased profit per animal. Regarding the characteristics of the animals' ingestive behavior, there was an increasing linear increase (P≤0.05) in the number of meals and linear decrease (P≤0.05) in the meal time, as the residue levels increased. The other behavioral characteristics were not influenced by the substitution levels. When the non-carcass characteristics of feedlot sheep with increasing levels of soybean pre-cleaning waste as a source of roughage in replacement of sorghum silage were evaluated, the liver, pancreas, thymus and kidneys showed increasing linear behavior as the levels of residue. When the filling of the gastrointestinal tract was evaluated, there was no effect of sorghum silage substitution by soybean pre-cleaning waste, except for the rumen and small intestine, which presented decreasing linear behavior as the substitution levels increased. Carcass characteristics were not influenced by the use of soybean pre-cleaning waste. Therefore, total replacement of sorghum silage by soybean pre-cleaning waste as roughage in the confined lambs diet can be recommended.